KEWENANGAN WALI DALAM MENENTUKAN PERNIKAHAN JANDA YANG BELUM DEWASA MENURUT IMAM AL-SYAFI'I - rahmat ari aripin (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
A woman who has never been married. The mariage must be approved by her legal guardian, namely her father or grandfather. A woman who wants to get married must have a legal guardian. The guardian in the school of Imam Al-Shafi‟i is one of the requirements that must be fulfilled. A father may arrange a marriage for a virgin woman with a man who is at the same level without her permission whether she is still immature or mature by having a comparable dowry. In other words, she may be forced by her legal guardian, father or grandfather, to get married without her permission. However, for a widow who is immature, Imam Al-Shafi‟i stated that her father should not force her to get married before she is mature. Imam Al-Shafi‟i prohibits the guardian in this case is a father to arrange a marriage for an immature widow because Imam Al-Shafi‟i adheres to the virginity. A mature woman may be forced while an immature widow may not be forced because the widow is considered to be no longer a virgin.